PENGEMBANGAN MEDIA LAPBOOK UNTUK MENDUKUNG PEMBELAJARAN PAI DI SEKOLAH DASAR - Maulana, Ikhsan; Aisyah, Aisyah; Wahyuni, Sri; Supiati, Supiati; Furqan, Al; Danil, M.; Aldyza, Nadia (Universitas Trunojoyo Madura, 2024)
This research is motivated by the tendency of students' learning outcomes to be low in the topic of the human skeleton and its functions. As a teacher, there is often a feeling of not having maximized the potential learning outcomes of students, leading to a tendency for students to be more passive. The researcher offers a solution through Discovery Learning and inquiry-based learning. The purpose of this study is to determine the effect of implementing Discovery Learning and inquiry-based learning on the learning outcomes of Grade IV students at UPTD SD Negeri 6 Peusangan Selatan on the topic of the human skeleton and its functions. The population in this study consists of all Grade IV students at UPTD SD Negeri 6 Peusangan Selatan, totaling 30 students across two classes. The sample includes all students from Class IVA, consisting of 15 students, and Class IVB, also consisting of 15 students. Class IVA was designated as the experimental class taught using Discovery Learning, while Class IVB served as the control class taught using inquiry-based learning. Data collection was conducted using tests, and data analysis employed t-test analysis. The results of the study on Grade IV students at UPTD SD Negeri 6 Peusangan Selatan, which examined the use of Discovery Learning and inquiry-based learning models and their impact on students' learning outcomes, indicate that the hypothesis results show that tcalculated is greater than ttable at a significance level of 0.05 (1.701). Mathematically, 2.407 more than 1.701, indicating that the application of Discovery Learning and inquiry-based learning significantly affects the learning outcomes of Grade IV students at UPTD SD Negeri 6 Peusangan Selatan in the topic of the human skeleton and its functions.